PENGARUH EWOM DAN DAYA TARIK WISATA DALAM MENENTUKAN KEPUTUSAN BERKUNJUNG PADA EKOWISATA KAMPUNG BLEKOK DI KABUPATEN SITUBONDO DENGAN MINAT BERKUNJUNG SEBAGAI VARIABEL INTERVENING - Rahmansyah, Maulidy; Kusnadi, Edy; Harisandi, Yudhistira (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is an interconnected activity between companies and consumers as a system to generate profits, for that the existence of the right marketing strategy can improve especially as a means of promotion, especially in the development of tourism in Kampung Blekok in Situbondo Regency. The purpose of this study was to analyze and examine the effect of Electronic word of mouth (EWOM) and tourist attraction in determining the decision to visit with interest in visiting as an intervening variable. The population in this study are visitors to Ecotourism Village Blekok in Situbondo Regency. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Electronic word of mouth (EWOM) has a significant positive effect on Visiting interest, Tourist attraction has a significant positive effect on Visiting interest, Electronic word of mouth (EWOM) has a positive significant effect on Visiting decisions, Tourist attraction has a significant positive effect on Visiting decision. Interest in visiting has a significant positive effect on Visiting decisions. The results of the indirect influence hypothesis show that the Electronic word of mouth (EWOM) variable on the Visiting decision through interest in visiting has a significant positive effect, Tourist attraction on the Visiting decision through interest in visiting has a positive but not significant effect.